'The luxury market in Brazil: an analysis of its complexity' - Ruggiero, Lorenzo de (2017)
The aim of the present research thesis is to investigate the luxury market in Brazil and how brand can survive in such context. All over the world this sector is becoming more and more crucial, due to many factors, such as the opening to new markets (Asia, Middle-East and so on), the increasing purchase power of consumers and the presence of much more differentiated products. After having clarified the definition of luxury and of its implications, the thesis will indeed present a global market analysis of the current situation and of the future trends. However, in Brazil luxury’s sector is facing challenging times, as the reports provided by consulting firms demonstrate. In fact, the profile of the Brazilian consumer is very peculiar and so it requires strategies ad-hoc. Moreover, the challenges of the market are many such as the attitude of spending outside Brazil, the counterfeiting, the high interest rates and many others. By the way, Brazil also represents a unique opportunity for international and local luxury brands, given to its increasing wealth and to a youthful generation of shoppers. That’s why, the thesis will also provide some effective tools for luxury companies to overcome the difficulties of the market and to catch all its potentials. As integration, practical cases of foreign luxury brands entering in Brazil are provided (Diesel, Zara, C&A and l’Occitane): these firms had found successful way to exploit the Brazilian market. Finally, the research deals with the case of the only Brazilian luxury brand able to expand outside: H. Stern. Leveraging on this experience, useful strategic insights could be provided to brands willing to follow this path. Leveraging on this experience, useful strategic insights could be provided to brands willing to follow this path. This experience is analysed through a conceptual framework about Internalization’s strategies provided at the beginning of the research thesis.